Ergonomic Benefits From a Laparoscopic Instrument With Rotatable Handle Piece Depend on the Area of the Operating Field and Working Height. (November 2017) - Steinhilber, Benjamin; Reiff, Florian; Seibt, Robert; Rieger, Monika A.; Martus, Peter; Kraemer, Bernhard; Rothmund, Ralf
Objective: To evaluate the effect of a laparoscopic instrument with a 360° rotatable handle piece (rot-HP) on biomechanical stress and precision in different areas of a simulated operating field at two working heights. Background: Surgeons performing laparoscopic procedures are exposed to biomechanical stress and have an increased risk of musculoskeletal complaints. Method: Fifty-seven healthy subjects (27 men, median age 26) without experience in laparoscopy performed a precision task in four quadrants (A–D) of the operating field using the rot-HP or a common fixed handle piece (fixed-HP) at an individually adjusted lower or higher working height. Biomechanical stress was assessed by surface EMG, wrist joint angles, and arm postures and precision by the number of mistakes. Results: Using the rot-HP reduced muscle activity of the biceps brachii and flexor carpi radialis muscle. An interaction of flexor activity and area of the operating field occurred with the lowest activity in Quadrant C. Wrist joint angles were more neutral using the rot-HP, especially when the lower working height was applied and in Quadrants B and C. However, increased wrist dorsal flexion occurred in Quadrant A while using the rot-HP. Arm postures and precision were less affected. Conclusion: The rot-HP allows some reductions of stresses in the arm and hand region, whereas the stress in the shoulder neck region is not modified. Application: The instrument's position and the working height may have to be considered as mediatory factors when describing the effectiveness of an ergonomic handle design for laparoscopic instruments.